Multicultural citizenship a liberal theory of minority rights - Kymlicka, Will 1962- (Clarendon, 1995)
However, Professor Kymlicka emphasizes that no single formula can be applied to all groups, and that the needs and aspirations of immigrants are very different from those of indigenous peoples and national minorities. The book discusses issues such as language rights, group representation, land claims, federalism, and secession - issues which are central to understanding multicultural politics, but which have been surprisingly neglected in contemporary liberal theory
Keywords: Burgerrechten; Collectieve rechten; Etnische minderheden; Groupes ethniques - Droits; Libéralisme; Minorités - Droits; Minorités - Statut juridique; Multiculturalisme; Multiculturele samenlevingen; Multiculturisme; Nationalités - Statut juridique; Minderheit; Ethnic groups -- Civil rights; Liberalism; Minorities -- Civil rights; Multiculturalism; Nationale Minderheit; Minderheitenrecht; Nationalstaat; Multikulturelle Gesellschaft